Activation and Modulation of Mast Cells (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Mast cells, which play critical roles in IgE-mediated immediate allergic responses, have recently been found to be involved in much broader immune responses, a fascinating process of which is partly depicted in this volume.